Bio-waste wood-derived porous activated carbon with tuned microporosity for high performance supercapacitors. (15th August 2022) - Selvaraj, Aravindha Raja; Chinnadurai, Deviprasath; Cho, Inho; Bak, Jin-Soo; Prabakar, Kandasamy
Abstract: In this study, we have processed renewable waste sticks/woods into eco-friendly porous activated carbon (AC) for renewable energy storage systems. The electrochemical behaviors of porous AC synthesized by chemical activation methods are studied in 6.0 M KOH electrolyte for supercapacitor application. The activation and pyrolysis treatments play a vital role not only in controlling the microstructure of the AC but also in improving the degree of graphitization and porosity. The AC processed at a pyrolysis temperature of 800 °C (AC-800) shows hierarchical porous nature with the largest pore volume of 0.75 cm 3 g −1 and the highest specific surface area of 973 m 2 g −1 . The AC-800 electrode has good capacitive performance of 408 F g −1 at a current density of 0.5 A g −1 and has a superior rate characteristic along with excellent electrochemical stability. The two-electrode symmetric device excelled with a specific capacitance of 133 F g −1 at a current density of 1 A g −1 in neutral aqueous electrolyte and a high energy density of 20.6 W h kg −1 due to an extended potential window. The waste birchwood (popsicle sticks) can be used as a promising low-cost precursor for the fabrication of supercapacitors.